The Indirect Impact of the Board of Directors' Composition on the Firm's Performance: An International Comparison - Ghazi, Zouari; Rim, Zouari-Hadiji (Asian Journal of Empirical Research, 2014)
As part of corporate governance theory, this article studies the relationship between the board of directors and the firm's performance from the angle of the R&D investment level in the international context. Our model seeks to show if the R&D investment level acts as a mediating variable between the internal mechanism of corporate governance and performance. This effect is sensitive to the national systems of governance. This empirical study is based on a sample of 174 U.S. and 179 Japanese firms for the period 2008-2012. The results of the linear regressions conducted showing the relationship between, on the one hand, the internal administrator and the non-dual structure, and on the other hand, the firm's performance, meditated by the firm's R&D investment-level.